Removal of heavy metals from simulated wastewater using modified rice husks / Fatihatul Nabila Sadon - Sadon, Fatihatul Nabila (2013)
Recently, the problems of heavy metal-contaminated wastewater have been classified as continuous and critical global issues due to toxicity effects of heavy metals towards environment and human health. Therefore, it has been identified that, the most promising technique to treat heavy metal-contaminated wastewater is adsorption by using activated carbon. However, due to major drawback posed by activated carbon particularly in terms of cost, the potential of rice husk as natural and low-cost adsorbent for the removal of heavy metals was investigated in this study. The main objective of this study was to characterize physical and surface properties of modified rice husk by using Elemental Analyzer, FESEM and BET. Besides that, the present study was also designed to determine the adsorption of heavy metals in single- and triple-layered fixed bed columns. In this investigation, the other aim was also to evaluate the effects of mechanical and multi-step chemical treatments on rice husk absorptivity. The heavy metals being studied are: Be, Ca, Cd, Cr, Cu, Fe, Li, Mg, Mn, Mo, Ni, Pb, Sb, Sr, Tl, V, and Zn. There are four types of rice husk adsorbents prepared in this study, namely Raw Rice Husk, Blended Rice Husk, Acetone-Benzene Treated Rice Husk (ABRH) and Acetone-Benzene-Methanol Treated Rice Husk (ABMRH). Surface morphology and BET analyses of ABRH and ABMRH revealed that the application of acetone, benzene, and methanol solvents able to open up internal surface area of top and bottom part of the pores, predicting a new structure of pore shape termed as Hypothetical T-shirt Pore Model. This pore shape exhibited larger pore diameters, higher porous and surface areas, as well as higher adsorption capacity, owing to its middle narrow section which reducing desorption rate. The theory of Hypothetical T-shirt Pore Model coincided with results obtained by adsorption studies based on numerical technique of area under the graph and removal efficiency analyses. Accordingly, the area under the graph analysis revealed that, the adsorption of heavy metals was significantly increased in the following order: Raw Rice Husk (Single-layered Bed) < Blended Rice Husk (Single-layered Bed) < Blended Rice Husk (Triple-layered Bed) < ABRH (Triple-layered Bed) < ABMRH (Triple-layered Bed).With respect to Raw Rice Husk in single-layered bed, the highest percentage reduction of area under the graph was demonstrated by ABMRH in triple-layered bed by 94.49%. Meanwhile, comparative study between single- and triple-layered fixed bed columns discovered that, the adsorption performance in triple-layered is notably increased compared to single-layered beds by 82.45% reduction of area under the graph. Hence, characterization analyses combined with demonstration of least total area under the graphs and highest adsorption capacity based on removal efficiency analysis emerged as a promising indication factor to justify the theory of Hypothetical T-shirt Pore Model. Thus, it was suggested that, hybrid modification of rice husk via mechanical and multistep chemical treatments enhanced the absorptivity of rice husk and thus demonstrated its potential as cost-effective adsorbent for the removal of heavy metals